Inhibition of Soluble Epoxide Hydrolase by Astaxanthin for Anti-Depressant Effects - Agboinghale, Precious (Université d'Ottawa / University of Ottawa, 2023)
The enzyme soluble epoxide hydrolase (sEH) plays a major role in the pathogenesis and pathophysiology of neurodegenerative diseases like depression by catalyzing the hydrolysis of epoxyeicosatrienoic acids (EETs) into dihydroxyicosatrienoicacids (DHETs), its less biologically active form, influencing the anti-inflammatory system and promoting inflammation. Therefore, inhibiting sEH leads to increased levels of EETs, reducing inflammation, especially in the brain and can help mitigate neurodegenerative diseases. This study investigated sEH inhibition by a phenolic carotenoid compound, astaxanthin and its inhibitory mechanism of action. Enzyme inhibitory activity and kinetics demonstrated that astaxanthin had a half-maximal inhibitory concentration (IC50) of 26 ± 0.92 μM and is a mixed-non-competitive inhibitor of sEH. In silico ADME/tox analysis showed that astaxanthin is bioavailable, biostable, and non-toxic when taken orally. Molecular docking study demonstrated that astaxanthin binds to an allosteric site of sEH and formed a contact and clashing-only interaction with the ASP333 residue of the hydrolase pocket of sEH. In this study, we highlight the potential therapeutic application of astaxanthin as a natural sEH inhibitor in the treatment of inflammation-related diseases, particularly neurodegenerative diseases.
Keywords: Depression; Astaxanthin; sEH; Enzyme kinetics; Enzyme Inhibition; EETs & DHETs